Subtle changes in chromatin loop contact propensity are associated with differential gene regulation and expression - William W. Greenwald (Nature Portfolio, 2019)
It is currently unclear how quantitative changes in chromatin loop propensity contribute to differential gene regulation. Here, the authors use phased Hi-C, RNA-seq, and ChIP-seq to show that subtle changes in loop propensity associate with differential gene regulation across cell types and haplotypes.